The use of construction and demolition waste in concrete in Cape Town - Wickins, Kyle (Department of Civil Engineering, 2015)
Incorporating recycled aggregates in concrete, despite the fact that effective technologies are available, is being adopted at a slow rate. These shortcomings have been associated with poor quality recycled aggregate (RA) products, lack of guidelines facilitating the use of RAs in various applications, and little incentive to incorporate these materials into civil engineering projects in Cape Town. In order to promote the use of RAs, a construction and demolition waste (C&DW) recycling culture has to be developed. Analysis of municipal waste data over the past 10 years shows that the commercial aggregate industry and market has not grown. A major contributor to the excess C&DW in the City, is the discarded C&DW once used to manage landfill sites with regard to activities such as cell creation, road building etc. This has resulted in 195 000 tons of the estimated 680 000 tons per annum (2012) of C&DW being disposed in Cape Town. The approach of the City and the construction industry to waste management is characterised by quality control issues, resource inefficiencies, economic and social burdens and environmental impacts. The realisation of C&DW as a resource and the development of on-site recycling procedures are seen as the key to creating more sustainable C&DW management systems. This is achieved internationally through detailed integrated waste management plans (IWMPs) that require waste generators to identify and separate a variety of C&DWs, as well as specify their proposed uses for these materials. This creates an environment where a specialist waste-processing sector can develop and practices such as the re-use and recycling of multiple C&DWs can flourish. It is important that the management and handling of C&DWs is carried out in a manner such that the technical requirements of this resource are understood. This study analyses two major C&D materials in clay and concrete masonry (CMA) materials and waste concrete (RCA). Greywacke stone is used as the control coarse aggregate. A 100% replacement ratio of coarse RA is used in all RA concrete mixes. A 50% Klipheiwel and 50% Dune sand mix is used in all concrete mixes respectively. C&D materials in this study were processed through simulated, on-site procedures to produce 19 mm coarse aggregate for concrete.